Method for trust analysis of exchange process behavior based on noninterference - Yi SUN; Xing-yuan CHEN; Xue-hui DU; Cheng LEI (Tongxin xuebao)
Aiming at the problem of dynamic data security exchange behavior cannot be controlled,methods for trusted analysis of exchange process behavior based on noninterference are proposed.First,the exchange behavior model is for-malized from the perspective of the exchange process.Then,the exchange behavior trust constraint rules,exchange be-havior trust judgment theorem and security proof are given in different stages and different mode.Finally,a concrete ap-plication example shows the availability of the method.